Female linguistic analysis in the 21st Century: the speech of Cynthia Viteri - Román-Jaramillo, Miguel (2020)
The aim of this article is to present through practical examples a discourse analysis of Dr. Cynthia Viteri, who was considered as the subject of this analysis because she is actually one of the most prominent women in Ecuadorian politics and the highest authority of the city of Guayaquil, Ecuador. Linguistic anthropology, sociolinguistics, the new dialectology and what in the Anglo-Saxon field is called "feminist linguistics" have been providing data for decades to show, in terms of how to use the languages, the way men and women construct and manifest themselves differently. This research work has a descriptive approach, and it was developed through the continuous observation of videos and conferences issued by the current mayor of Guayaquil, Dr. Cynthia Viteri Jiménez, which are reproduced through the YouTube channel and correspond to the months between January and November 2019. The linguistic analysis shows the combination and connection of expressions that externalize the communicative acts. Greater emphasis is placed on linguistic forms such as lexicon, reference, coherence (argumentation), the interaction of semantics and syntax (modality, aspects, time, negation, modification adverbial, etc.), as well as the speaker’s body language manifestations. Although, it is possible to observe that the gender differences are a fundamental fact of human life and it is not surprising to find them reflected in language; therefore, attention to the use of language in the social context is very important.